Insights into Underrail Rubber Pad’s Effect on Vehicle-Track-Viaduct System Dynamics - Linya Liu; Zhiyuan Zuo; Yunlai Zhou; Jialiang Qin; Zhenyu Niu (Shock and Vibration)
To scientifically characterize the dynamic mechanical characteristics of the rubber pad under the rail of fasteners and its influence on the dynamic response of the vehicle-rail-viaduct system, taking the rubber pad under the rail of WJ-7B high-speed railway (HSR) with constant resistance as an example, a TFDV model was applied to characterize the viscoelasticity of the rubber pad and the theoretical model in the dynamic coupling of vehicle-rail-bridge was also studied. The results show that the energy storage modulus and loss factor of rubber pad under rail show a curved surface relation versus the change of frequency-temperature. In a certain frequency/temperature range, the energy storage modulus and loss factor of rubber pad under rail increase with the decrease of temperature and the increase of frequency, and the influence of low temperature on dynamic parameters is more significant. With the decrease of temperature, the minimum value of total dynamic flexibility decreases, and the corresponding extreme frequency shifts to high frequency. Viscoelastic dynamic features of rubber pad under rail mainly affect the dynamic response of vehicle subsystem and rail-bridge subsystem. With the decrease of ambient temperature of rubber pad, the dominant frequency band of power spectrum curve of each structure shifts to high frequency.